Evaluation of Building Maintenance: A Case Study in UTHM Campus Pagoh - MD OTHMAN, ANIS AISYAH; ABU BAKRI, NUR IZZAH; MOHAMED YACOOB, NURUL NASIHA BANU; AHMAD, NOR FARAH ATIQAH (Multidisciplinary Applied Research and Innovation, 2026)
Building maintenance is essential guaranteeing the durability, usability, and security of educational facilities. This study assesses the condition of building at UTHM Campus Pagoh by identifying defects such as cracks, water leaks, peeling paint, molds and termite infestation. Visual inspections conducted on-site and defects documentation using standardized checklists were all part of the research process. A Risk Assessment Matrix was used to further analysze the data and rank the maintenance requirements according to likehood and severity. The most common and serious flaws that need to be fixed right now, according to the results, are structural cracks and water leaks. To enhance the general safety, comfort and functionality of the buildings, is recommend to emphasizes the necessity of proactive inspection schedules, systematic maintenance planning, and efficient resource allocation. The creation of a more reliable and sustainable maintenance management system at UTHM Campus Pagoh is encouraged.